Finding purpose in life: the way of the masters' athletes - Daniel Vicentini de Oliveira; Cristina Cristovão Ribeiro; Simone Fiebrantz Pinto (Brazilian Society of Geriatrics and Gerontology, 2024)
Increasing longevity poses major challenges for society and older persons, highlighting the importance of identifying factors that promote healthy aging and the maintenance of functional abilities. Among these factors, psychological well-being - particularly purpose in life - is crucial. Purpose in life (PL) is associated with a positive worldview and emotional well-being. The literature suggests that the perception of higher PL can act as a protective factor against conditions such as stress and depression, motivating older individuals to take better care of their physical and mental health. Furthermore, involvement in sports, especially among masters' athletes, not only promotes physical health but also strengthens a sense of community and purpose. For these individuals, sport is not just a form of physical exercise, but a continuous source of challenges, social connection, and inspiration. Thus, discovering and cultivating purpose in older age not only improves individual quality of life, but also inspires others to adopt active and meaningful lifestyles, challenging conventional expectations of aging.